Analysis of α-Dystroglycan/LG Domain Binding Modes: Investigating Protein Motifs That Regulate the Affinity of Isolated LG Domains - Dempsey, Christopher E.; Bigotti, Maria Giulia; Adams, Josephine C.; Brancaccio, Andrea (Frontiers in Molecular Biosciences, 2019)
Dystroglycan (DG) is an adhesion complex that links the cytoskeleton to the surrounding extracellular matrix in skeletal muscle and a wide variety of other tissues. It is composed of a highly glycosylated extracellular alpha-DG associated noncovalently with a transmembrane beta-DG whose cytodomain interacts with dystrophin and its isoforms. Alpha-dystroglycan (alpha-DG) binds tightly and in a calcium-dependent fashion to multiple extracellular proteins and proteoglycans, each of which harbours at least one, or, more frequently, tandem arrays of laminin-globular (LG) domains. Considerable biochemical and structural work has accumulated on the alpha-DG-binding LG domains, highlighting a significant heterogeneity in ligand-binding properties of domains from different proteins as well as between single and multiple LG domains within the same protein. Here we review biochemical, structural and functional information on the LG domains reported to bind alpha-dystroglycan. In addition, we have incorporated bioinformatics and modelling to explore whether specific motifs responsible for alpha-dystroglycan recognition can be identified within isolated LG domains. In particular, we analysed the LG domains of slits and agrin as well as those of paradigmatic alpha-DG non-binders such as laminin-alpha3. While some stretches of basic residues may be important, no universally conserved motifs could be identified. However, the data confirm that the coordinated calcium atom within the LG domain is needed to establish an interaction with the sugars of alpha-DG, although it appears that this alone is insufficient to mediate significant alpha-DG binding. We develop a scenario involving different binding modes of a single LG domain unit, or tandemly repeated units, with alpha-DG. A variability of binding modes might be important to generate a range of affinities to allow physiological regulation of this interaction, reflecting its crucial biological importance.